Epidemiology of binge eating disorder: prevalence, course, comorbidity, and risk factors. Issue 6 (7th November 2021) - Keski-Rahkonen, Anna
Abstract : Purpose of review: Binge eating disorder (BED) is a new diagnosis in the Fifth Edition of the Diagnostic and Statistic Manual of Mental Disorders (DSM-5) and the Eleventh Revision of the International Classification of Diseases (ICD-11). Recent findings: DSM-5 BED is currently estimated to affect 1.5% of women and 0.3% of men worldwide; a lifetime diagnosis of DSM-5 BED is reported by 0.6–1.8% of women and 0.3–0.7% of men. In adolescence, BED is even more prevalent, but often transient. Many adults with BED report longstanding symptoms; less than half are recognized in healthcare. Commonly co-occurring conditions include obesity, type 2 diabetes, and hypertension. In a nationally representative US-based study, up to 23% of individuals with BED had attempted suicide, and virtually all (94%) reported lifetime mental health symptoms: 70% mood disorders, 68% substance use disorders, 59% anxiety disorders, 49% borderline personality disorder, and 32% posttraumatic stress disorder. Data on mortality are scarce, but the standardized mortality ratio of BED is estimated to be 1.5–1.8. Various minority statuses, deprivation, violence, trauma, and major mental illness may increase the risk of BED. Summary: BED is often invisible and overlooked, perhaps due to societal biases. For this reason, prevention, detection, and management of BED are closely linked with social justice and equity.